FRB 121102: Drastic changes in the burst polarization contrasts with the stability of the persistent emission. Issue 4 (24th February 2022) - Plavin, A; Paragi, Z; Marcote, B; Keimpema, A; Hessels, J W T; Nimmo, K; Vedantham, H K; Spitler, L G
ABSTRACT: We study milliarcsecond-scale properties of the persistent radio counterpart to FRB 121102 and investigate the spectro-polarimetric properties of a bright burst. For the former, we use European VLBI Network (EVN) observations in 2017 at 1.7 and 4.8 GHz. For the latter, we reanalyse the 1.7-GHz data from the 100-m Effelseberg telescope taken in 2016. These observations predate other polarimetric studies of FRB 121102, and yield the highest burst Faraday rotation measure (RM) to date, RM = 1.27 · 10 5  rad m −2, consistent with the decreasing RM trend. The fractional polarization of the burst emission is 15 per cent at 1.7 GHz. This can be reconciled with the high-fractional polarization at higher frequencies if the Faraday width of the burst environment is 150 rad m −2 – a bare 0.1 per cent of the total Faraday rotation. The width may originate from minor non-uniformities in the Faraday screen, or from effects in the emitting region itself. The upper limit on the persistent source size is 1 pc, barely consistent with a young supernova (SN) scenario. The flux variability limit of $\lt 10{{\ \rm per\ cent}}$ is not in favour of the young SN scenario, and challenges other interpretations as well. The fractional polarization of the faint persistent source is constrained at $\lt 25{{\ \rm per\ cent}}$ at 4.8 GHz ruling out a common origin with the highly polarized individual bursts.